Hubungan Kontrol Diri Dengan Kecanduan Game Online Pada Remaja Dilingkungan Jl.Enggang Perumnas Mandala Medan - Novelisda Zai; Abdul Munir (Universitas Medan Area, 2022)
The purpose of this research is to find out the correlation between self-control and online game addiction in teenagers environment Jl. Enggang Perumnas Mandala Medan. This research uses quantitative research methods. The research hypothesis is there is a positive relationship between online game addiction in teenager environment Jl. Enggang Peumnas Mandala Medan. This studi uses a total sampling technique in teenagers environment Jl. Enggang Perumnas Mandala Medan consisting 75 teenagers. The scale method used in this was online game addiction and self-control scale. The data analysis used in this research was product moment with the help of computer program for MS. Windows version 22. The results of data analysis show that the value of the correlation coefficient (r)0,557 and significant (p) = 0,000 wich means p 0,05 there is a correlation between online game addiction and self-control in teenagers environment Jl. Enggang Perumnas Mandala Medan. Variable online game addiction has an empirical average (RE) 141,93 and a hypothetical is (RH) 117 means that online game addiction is high, variable self-control has an empirical average (Re) 87,41 and a Hypothetical is (RH) 77 means that self-control is moderate.